2022
DOI: 10.1038/s41598-022-10399-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in contrast sensitivity after surgery for intermittent exotropia

Abstract: To determine whether intermittent exotropia (IXT) surgery affects contrast sensitivity (CS), this retrospective study evaluated the changes in monocular and binocular CS and the binocular summation ratio (BSR) quantified as the ratio between the values of the binocular and the better monocular CS score (BSR = binocular CS score/better monocular CS score) after surgery for IXT. The subjects were patients who had undergone IXT-correcting surgery with a postoperative follow-up of > 3 months and had pre- and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In the previous studies, the BSR was usually adopted as the evaluation parameter for the BiS phenomenon of CS, but the calculation methods were different such as BSR = BCV/MCV [ 8 , 10 , 20 ], or BSR = BCV 2 /(RCV 2 + LCV 2 ) [ 12 ]. There also existed differences in evaluation methods such as sinusoidal grating [ 12 , 20 ], Mars contrast sensitivity test [ 8 , 10 ], etc. The animal experiments demonstrated that neurons in the lateral geniculate nucleus of strabismic amblyopia were only damaged at high spatial frequencies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, the BSR was usually adopted as the evaluation parameter for the BiS phenomenon of CS, but the calculation methods were different such as BSR = BCV/MCV [ 8 , 10 , 20 ], or BSR = BCV 2 /(RCV 2 + LCV 2 ) [ 12 ]. There also existed differences in evaluation methods such as sinusoidal grating [ 12 , 20 ], Mars contrast sensitivity test [ 8 , 10 ], etc. The animal experiments demonstrated that neurons in the lateral geniculate nucleus of strabismic amblyopia were only damaged at high spatial frequencies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…BiS can be influnced by multiple factors such as age, interocular difference of visual acuity, and eye position [ 4 8 ]. Successful strabismus surgery can improve BiS in strabismus patients [ 9 ], which might be related to eye position control and stereopsis [ 10 13 ]. BCS in strabismus patients was significantly lower than monocular contrast sensitivity, especially at 6 cpd spatial frequency, which was not correlated with the degree of strabismus, gender, age, refraction error, stereopsis, and duration of IXT [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, the BSR was usually adopted as the evaluation parameter for the BiS phenomenon of CS, but the calculation methods were different such as BSR = BCV/UCV [8,10,20] , or BSR = BCV² /(RCV² + LCV²) [12] . There also existed differences in evaluation methods such as sinusoidal grating [12,20] , Mars contrast sensitivity test [8,10] , etc. The animal experiments demonstrated that neurons in the lateral geniculate nucleus of strabismic amblyopia were only damaged at high spatial frequencies [21] .…”
Section: Discussionmentioning
confidence: 99%
“…CSF of amblyopia patients with fusion function was impaired at intermediate and high frequencies, presenting a higher proportion of BiS than strabismus patients without fusion function [8] . Young's study revealed that the BSR of IXT patients was temporarily decreased 1 month postoperatively, which may be due to postoperative foreign body sensation, lacrimation, and conjunctival edema, and then it returned to the preoperative level 3 months after surgery [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation